Memórias e processos identitários: estudo antropológico sobre o sentimento de pertencimento entre os moradores da Colônia Treze - Carvalho, Gil Marcos dos Santos (2022)
This dissertation briefly analyses the history of the village Colonia Treze, its formation process over the years, the emergence of COOPERTREZE and its importance for the economic, social and political development of the village. In addition, it is theoretically inserted in the debates on the formation of cities, memories and identity processes of Treze. The research also showed how Inspector Luiz Alves used the Israeli model - Kibbutz - in 1965, in order to recover the cooperative. With this, it began to contribute in a more organised way to the process of formation of settlers, applying the example of Israel, which aimed at an integral cooperativism in which the members were not only concerned with economic issues, but with better quality of life; this, based on meeting economic, social and cultural needs through efficient and democratic welfare. This integrated management model provided a process of training cooperative members, that is, they took technical improvement courses and citizenship classes that made them more participatory in discussions related to community difficulties.